Comparison of Cerebral Blood Flow Acquired by Simultaneous [15O]Water Positron Emission Tomography and Arterial Spin Labeling Magnetic Resonance Imaging. Issue 8 (August 2014) - Zhang, Ke; Herzog, Hans; Mauler, Jörg; Filss, Christian; Okell, Thomas W; Kops, Elena Rota; Tellmann, Lutz; Fischer, Thomas; Brocke, Burkhard; Sturm, Walter; Coenen, Heinz H; Shah, N Jon
Until recently, no direct comparison between [ 15 O]water positron emission tomography (PET) and arterial spin labeling (ASL) for measuring cerebral blood flow (CBF) was possible. With the introduction of integrated, hybrid magnetic resonance (MR)-PET scanners, such a comparison becomes feasible. This study presents results of CBF measurements recorded simultaneously with [ 15 O]water and ASL. A 3T MR-BrainPET scanner was used for the simultaneous acquisition of pseudo-continuous ASL (pCASL) magnetic resonance imaging (MRI) and [ 15 O]water PET. Quantitative CBF values were compared in 10 young healthy male volunteers at baseline conditions. A statistically significant ( P <0.05) correlation was observed between the two modalities; the whole-brain CBF values determined with PET and pCASL were 43.3 ±6.1 mL and 51.9 ± 7.1 mL per 100 g per minute, respectively. The gray/white matter (GM/WM) ratio of CBF was 3.0 for PET and 3.4 for pCASL. A paired t -test revealed differences in regional CBF between ASL and PET with higher ASL-CBF than PET-CBF values in cortical areas. Using an integrated, hybrid MR-PET a direct simultaneous comparison between ASL and [ 15 O]water PET became possible for the first time so that temporal, physiologic, and functional variations were avoided. Regional and individual differences were found despite the overall similarity between ASL and PET, requiring further detailed investigations.